Influence of worry on sustained attention to emotional stimuli: Evidence from the late positive potential. (19th February 2015) - Burkhouse, Katie L.; Woody, Mary L.; Owens, Max; Gibb, Brandon E.
Highlights: When women viewed emotional pictures, LPPs were largest for threatening stimuli. Worry was positively correlated with LPPs to emotional, but not neutral, stimuli. Link between worry and threat/positive stimuli maintained controlling for anxiety. Abstract: There is preliminary evidence to suggest that worry is associated with dysregulated emotion processing resulting from sustained attention to emotional versus neutral stimuli; however, this hypothesis has not been directly tested in prior research. Therefore, the current study used the event-related late positive potential (LPP) to directly examine if high levels of trait worry moderate sustained attention to emotional versus neutral stimuli. Electroencephalogram data was recorded while twenty-two women passively viewed neutral, positive, dysphoric, and threatening emotional images. Consistent with our hypotheses, higher levels of worry were associated with larger LPP amplitudes for emotional images but not neutral images. Importantly, the positive correlations between trait worry and LPP responses to threatening and positive images were maintained even when controlling for the influence of current anxiety symptoms, suggesting that worry may influence emotion processing whether or not the person is currently anxious. This sustained attention to emotional information may be one mechanism underlying how trait worry increases risk for anxiety disorders.